Respuesta :

First of all. let's write the system in standard form:


[tex] \left \{ {{-x+2y=6} \atop {-x+6y=18}} \right. [/tex]


We can subtract the first equation from the second to get


[tex] 4y=12 [/tex]


and thus


[tex] y=3 [/tex]


Now we can substitute this value for [tex] y [/tex] in any of the equations to find the value for [tex] y [/tex]: if for example we choose the first equation, we have


[tex] -x+2\cdot3 = 6 \iff -x+6=6 \iff x=0 [/tex]

Answer:

For those of you doing unit 7 lesson 2 solving systems using substitution questions 1-4

Step-by-step explanation:

1. B

2. C

3. C

4. B